Manage the legal risks - Zulhuda, Sonny (2020)
We were reminded by the Prime Minister, Tan Sri Muhyiddin Yassin, to ensure continued education with new methods of online and remote teaching and learning (RTL). He said this must be strengthened as e-learning is the future of education. Teachers and lecturers must develop their skills with this new normal. With the necessary skills and knowledge, RTL will not be less fun and interesting. However, being unfamiliar with how technology works may lead to some legal complications. Therefore in conducting RTL, educators also need to be careful so as not to end up in a legal mess with potential liabilities.